Perancangan produk interior modular berbahan upcycling kayu bekas palet - Venlista Suprapto; Yusita Kusumarini; Frenky Tanaya (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
The flow of containers in the terminals of the Port of Tanjung Perak Surabaya has increased. The increased container flow has an impact on the pilling up of ex-wood pallets and if this left continuously it become city trash. Even though ex-wood pallets have the characteristics and potential to be developed, for that we have do upcycling. In addition, people who live in narrow homes usually discarded or replaced their old interior products because they do not fit into the new space. Therefore, people need a modular interior product that can be assembled from scratch, and can be arranged according to the needs and desires of the user, by doing upcycling to reduce the pilling up of ex-wood pallets. The design aims to knowing the characteristics and potential of ex-wood pallets, then reused into modular interior products with modules that accordance with their characteristic. The modules are connected using connectors, which can be assembled according to the user’s needs. Design thinking methods consisting of inspiration, ideation, and implementasion are carried out in this design process. The results of this design are modules and connectors that can be assembled into 12 types of products, media promotion, and booth design. This design proved that ex-wood pallets have characteristics and potential that can be develop by upcycling into modules in accordance with the characteristics of used wood pallets that can be assembled using connector into a variety of modular interior products according to the needs and desires of the user.